The Contribution of Credit Assistance For the Working Capital of the Traditional Food Production in Airmadidi County, of the North Minahasa Sub-Region - Soewignyo, Fanny (JBE (Journal of Business and Economics); Volume 5 No.2, 2006 JBE UNKLAB, 2006)
Theis study aims to look into the contribution and barriers of funding small-scale traditional food industry in Kecamatan Airmadidi Kabupaten Minahasa Utara to identify sources of funds used by the enterpreneurs such as: personal savings, relatives, suppliers, and banks. This research study utilized the descriptive metH0d to analyze the sources of funds, uses of funds, and the barriers in attempting to develop the business. Data gathering was done using lirary research, questionnaire and supplemented by personal interview. Small-scale traditional food industry represents one of several small-scale industrirs as source of income of the society in Kecamatan Airmadidi, Kabupaten Minahasa Utara. This industry supports the economic growth of this area but it must be supported by the goverment and otherrelated intitutions in its attempt to increase production volume, quality, and market network to grow. It is found from this study that additional funds is needed to finance the operations and investments. Currently enterpreneurs do the business using their limited personal savings. Generally, small-scale industry such as traditional food industry must be supported to grow and the supports given by any related institutions could affect this industry to grow, increase employment and enhance standard of leaving of the society to survive in the economic crisis which is still in process to recover.